Small molecules as efficient hole-transport materials for inverted perovskite solar cell - Tan, Marvin Wen Bin (2018)
This project aims to provide a comprehensive study to incorporate small molecules as a hole transport layer for inverted perovskite solar cells. Upon generation of electron-hole pairs in the perovskite layer, the hole transport layer provides a pathway for the transport of holes away towards the cathode. Three materials were studied on the suitability and efficiency to be used as the hole transport layer. These materials (DPA-2,6-ANR-DPA; TPA-2,6-ANR-TPA; TPA-NADT-TPA) are studied and experimented on spin-rate and concentration. Experiments have shown promising results for future incorporation of such molecules into solar cells to improve the efficiency and performance. The optimal spin rate were determined to be 3000 rpm and the concentration of the hole transport material determined to be 5mg/ml.